Synthesis of 4,4′-Diacryloylphenyl Ether to Conveniently Crosslink Sulfonated Poly(ether ether ketone) Membranes via Electron Beam Irradiation - Lee, Eun-Byul; Kang, Naeun; Shin, Junhwa; Lee, Youn-Sik (Bulletin of the Korean Chemical Society, 2015)
4,4′‐Diacryloyldiphenyl ether (DAPE), a nonhydrolizable crosslinking agent, was synthesized in a moderately high yield, and used for successful crosslinking of a highly sulfonated poly(ether ether ketone) membrane. This study indicates that DAPE can be conveniently used to crosslink ionic aromatic hydrocarbon polymer membranes.